Service-Learning as a Mechanism to Prepare School Psychology Graduate Students: A Case Example. - McPherson, Casey; Karahalios, Vicky; Shriberg, David (Trainers' Forum, 2017)
An ongoing challenge in the preparation of school psychologists, particularly in the first year of graduate training, is finding learning experiences that provide students with an opportunity to apply foundational skills, such as consultation and data-based decision-making, in a culturally responsive manner. Service-learning is a well-established teaching mechanism designed to address just this need, yet there is scant scholarship on ways to utilize this methodology in school psychology training. This manuscript describes a service-learning experience at an urban tutoring center in which first-year school psychology Ed.S. and Ph.D. students gathered agency-wide comprehensive academic screening data and provided targeted consultation support in the area of reading comprehension to identified fourth- through sixth-grade students and their tutors. Indicators of the positive impact of this work across stakeholder groups is provided.
Keywords: dept.csp

Socioeconomic Status - Foss-Kelly, Louisa; Baycroft, Jessica (The SAGE Encyclopedia of Marriage, Family, and Couples Counseling, 2017)
Keywords: dept.csp

Poverty and Family Develoment - Foss-Kelly, Louisa; Rand, Arden G. (The SAGE Encyclopedia of Marriage, Family, and Couples Counseling, 2017)
Keywords: dept.csp

Counseling Transgender Clients - Brammer, R.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The issues surrounding working with clients who experience a disconnect between their gender identity and their designated sex at birth are discussed. Gender and gender identity terminology are thoroughly discussed, including terminology that should be avoided. The complex issues surrounding terminology, gender, and changing terms are explored. The cultural history of third gender people, as well as the impacts of colonization, are discussed. Authors also present the prevalence and identity development of transgender persons. Transgender persons face a significant risk of experiencing bias incidents, indicating a significant increase in minority-based stress. Focusing specifically on transgender persons who wish to transition, the authors explore physical and mental health challenges that clients may face. Special considerations with the DSM and use of the Gender Dysphoria diagnosis, are explained. Affirmative counseling strategies, including preparation and counseling practices, with transgender persons are examined. Special attention is given to intersectional issues, such as age and ethnicity. © 2017 by the American Counseling Association. All rights reserved.
Keywords: ALGBTIC competencies; Affirmative counseling; Gender identity; Identity development; Intersectionality; LGBT; Mental health; Minority stress; Physical health; Third gender; Transgender; dept.csp

Counseling an LGBTQI+ Person of Color - Filmore, J.M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The intersectionality of ethnicity and affectional orientation is discussed within this chapter, with special attention given to specific challenges faced by queer people of color (QPOC). Four elements of African American culture that may negatively impact queer-identified persons are: heterosexism, masculinity, issues surrounding HIV, and the role of the Black Church. In Latin Americans, concepts of machismo and marianismo, Catholicism, familismo, and respeto, are discussed in terms of their impact on LGBTQI+ persons. Authors also discuss elements of Asian culture that will impact queer-identified Asians: stigma, complementarity, collectivism and conformity, and shame. The importance of culture specific counseling is underscored. © 2017 by the American Counseling Association. All rights reserved.
Keywords: African American; Asian American; Hispanic; Intersectionality; LGBT; Latin American; Queer person of color; dept.csp

Counseling Intersex Clients - Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Persons who are born with ambiguous or a combination of both male and female genitalia are referred to as intersex. The biological nature of intersex conditions, or disorders/differences of sex development, are reviewed in this chapter. Issues of bias for people who are intersex are discussed, as children are often made to feel abnormal and required to keep their difference a secret. Parents and families may also experience mental health symptoms, such as traumatic reactions, at their child's birth, when a gender cannot readily be assigned to their child. Although, doctors have (and some still continue) to recommend genital surgery without the child's consent, this is considered unethical by many advocacy organizations for intersex people. Physical issues and the standard of care recommended by advocacy organization and ALGBTIC are discussed. The role of a counselor working with a family with an intersex infant is discussed, as are specific counseling techniques for working with intersex clients of all ages. © 2017 by the American Counseling Association. All rights reserved.
Keywords: ALGBTIC competencies; Affirmative counseling; Difference of sex development; Disorders of sex development; Intersex; LGBT; dept.csp

Counseling Two-Spirit Clients - Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The term two-spirit refers to persons who identify as indigenous to the Americas and as having a gender and/or affectional variance. Historically recognized by most Native tribes, two-spirit persons were seen as a blessing to their tribe, having high social and spiritual value. Native spirituality and the history of two-spirit persons are explored within this chapter. Because of colonization, much of these traditional beliefs have been lost or distorted, leaving LGBTQI+ people within Native communities experiencing high levels of bias and abuse. Increased physical and mental health challenges due to these significant minority stressors are discussed. Specific counseling skills and techniques for working with this population are explored. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Affirmative counseling; LGBT; Native american; Queer person of color; Two-spirit; dept.csp

The Science of Gender and Affectional Orientation - Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Sex, gender, and affectional orientation are complex issues; scientific research has long investigated the etiology of gender variance and affectional orientation. Although some interpret this research as contributing to a viewpoint of LGBTQI+ as abnormal, biological research can also be viewed as a confirmation of the natural human variance and adaptability that different gender identities and affectional orientation serves. Research supporting a biological basis for sexual attraction, gender identity, and affectional orientation is presented. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Affectional orientation; Etiology; Gender identity; Gender variance; LGBT; Science; dept.csp

Physical and Mental Health Challenges Found in the LGBTQI+ Population - Ginicola, M.M.; Filmore, J.M.; Smith, C.; Abdullah, J. (Affirmative Counseling With LGBTQI+ People, 2017)
LGBTQI+ people face significant increased stress and marginalization surrounding their gender and/or affectional identities. The minority stress model (Meyer, 2003) serves as a helpful framework when understanding negative coping behaviors, and poor physical and mental health. Microaggressions, marginalization, discrimination, abuse, harassment, and experience of bias incidents all add to the LGBTQI+ person's stress. Intersectional identities may exponentially increase this stress, as is the case for queer persons of color. Authors consider general physical health and mental health risks for lesbian, gay male, bisexual, and transgender clients. Barriers to quality health care and protective factors are also covered. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Intersectionality; LGBT; Mental health; Minority stress; Physical health; dept.csp

Working With LGBTQI+ Clients Who Have Experienced Religious and Spiritual Abuse Using a Trauma-Informed Approach - Ginicola, M.M.; Filmore, J.M.; Stokes, M. (Affirmative Counseling With LGBTQI+ People, 2017)
Many LGBTQI+ clients have been explicitly harmed by religious leaders and those using religious doctrine. This experience can go beyond discrimination and oppression; a person may have experienced serious emotional and spiritual abuse at the hands of faith practitioner attempting to condemn affectional orientation and/or gender identity variance in order to comply with religious doctrine. The current religious conflict with LGBTQI+ issues is briefly reviewed. Authors define and explore spiritual abuse, as well as the experience of spiritual abuse as experienced by a LGBTQI+ person. Counseling challenges and strategies are described. Specifically, the use of a trauma informed counseling approach as applied to clients who have experienced spiritual abuse is explored. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Affirmative counseling; Counseling techniques; LGBT; Religion; Religious trauma; Spiritual abuse; Spirituality; Trauma informed approach; dept.csp

The Role of Religion and Spirituality in Counseling the LGBTQI+ Client - Ginicola, M.M.; Furth, B.H.; Smith, C. (Affirmative Counseling With LGBTQI+ People, 2017)
When religion or spirituality is present, it likely impacts the needs a LGBTQI+ person may bring to counseling. First, the LGBTQI+ person's identity development is likely altered in significant ways, either positively or negatively. Research on this topic is reviewed and the FAITH model for working with LGBTQI+ clients struggling with their faith is presented. Ethical issues arising between disaffirming religious beliefs and counseling LGBTQI+ clients are also reviewed. Authors review affirming and semi-affirming religious organizations within the United States. Additional counseling issues are also explored. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Affirmative counseling; Affirming religions; Counseling; Ethics; LGBT; Religion; Spirituality; dept.csp

Counseling Asexual Clients - Ginicola, M.M.; Ruggiero, A. (Affirmative Counseling With LGBTQI+ People, 2017)
Asexual persons experience little to no sexual attraction to others, although they may still experience romantic attraction and a desire to bond with others. Asexual people often experience bias and marginalization from allosexuals (persons who experience sexual attraction) within heterosexual and queer communities. Asexuals may also face bias from well-intentioned therapists who assume their lack of sexual attraction is due to trauma or a disorder. Although little research has been performed on counseling asexual persons, the authors review appropriate diagnostic counseling criteria for arousal and sexual disorders versus an asexual identity, and affirmative and strength-based techniques appropriate for work with this population. © 2017 by the American Counseling Association. All rights reserved.
Keywords: ALGBTIC competencies; Affirmative counseling; Asexual; LGBT; dept.csp

Counseling Gay Male Clients - Ginicola, M.M.; Sanabria, S.; Filmore, J.M.; DeVoll, M. (Affirmative Counseling With LGBTQI+ People, 2017)
The issues surrounding working with gay men in counseling are reviewed within this chapter. Prevalence, identity development, and relationships are explored. Gay males experience a significant amount of bias and discrimination; they are the largest single target of hate crimes within the LGBTQI+ population reported to the FBI every year. This risk is greater when intersectional minority identities are also present; more gay males are targets for hate crimes when they present as gender non-conforming, are men of color, as well as live in a rural area of the country. Authors explore physical and mental health issues related uniquely to gay male clients, as a result of the heightened minority stress. Affirmative counseling techniques for working with gay male clients is reviewed, with special attention given to developing counselor self-awareness, developmental counseling, and empowerment strategies. © 2017 by the American Counseling Association. All rights reserved.
Keywords: ALGBTIC competencies; Affirmative counseling; Counseling techniques; Gay male; Identity development; Intersectionality; LGBT; Mental health; Minority stress; Physical health; dept.csp

Developing Competence in Working With LGBTQI+ Communities: Awareness, Knowledge, Skills, and Action - Ginicola, M.M.; Smith, C.; Filmore, J.M. (Affirmative Counseling With LGBTQI+ People, 2017)
When providing counseling to a LGBTQI+ client, counselors must understand their ethical obligations, as well as attend to the multiple sets of counseling competencies. Using a multicultural and social justice counseling framework, counselors can situate their learning into very specific areas for LGBTQI+ clients: self-awareness of attitudes and beliefs, knowledge of issues faced by LGBTQI+ people, counseling skills, and action. Understanding common terminology, the history of the LGBTQI+ population, and modern issues faced by these communities can help lay the foundation for counselors working with LGBTQI+ persons. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Affirmative counseling; LGBT; LGBTQI+ clients; Multicultural counseling; Social justice; dept.csp

Preface - Ginicola, M.M.; Smith, C.; Filmore, J.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Keywords: dept.csp

Evidence-Based Practice for Counseling the LGBTQI+ Population - Goodrich, K.M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Authors review the current state of Evidence Based Practice (EBP) for counseling LGBTQI+ clients. Although there is an identified need for more research in this area, the research supports a general affirmative approach. Strategies for building rapport, assessment, and interventions are reviewed. Specific attention is given to the importance of cultural accommodations and adaptations of EBPs that have not been tested directly on the LGBTQI+ population. Authors also explore how integrative and creative therapies may hold helpful strategies for work with these communities. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Affirmative counseling; EBP; Empirically based practice; Evidence based practice; LGBT; dept.csp

Identity Development, Coming Out, and Family Adjustment - Goodrich, K.M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
LGBTQI+ youth face an identity struggle that is dissimilar to their heterosexual and/or cisgender peers. While family and community acceptance impacts the process of understanding one's own affectional orientation and/or gender identity, all LGBTQI+ persons typically engage in a process of understanding and eventually accepting their affectional and/or gender variance. The authors review LGBTQI+ Identity Formation Models, as well as the influence of intersectionality on identity. The benefits and challenges of coming out are explored, as counselors need to understand this delicate process and how to support clients who are considering coming out. Counselor work with families is also reviewed. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Coming out; Family; Identity development; Intersectionality; LGBT; LGBT youth; dept.csp

Counseling Bisexual/Pansexual/Polysexual Clients - Harper, A.J.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The issues surrounding working with clients who are predisposed to share affection with people from more than one gender. Terminology, as well as prevalence are discussed. Bisexual identity development and relationships are explored. Experiences of bias, including bisexual erasure, biphobia, and bisexual invisibility are discussed. Bisexuals may encounter monosexism and marginalization in both heterosexual and queer communities, among people who do not identify with non-binary identities. Intersectional identities can be subject to increased oppression. Authors explore how minority stress contributes to greater physical and mental health issues in bisexual clients. Although there has been little research on affirmative counseling techniques for bisexual clients, a general strength-based approach with feminist and social justice techniques is recommended. © 2017 by the American Counseling Association. All rights reserved.
Keywords: ALGBTIC competencies; Affirmative counseling; Bisexual; Identity development; Intersectionality; LGBT; Mental health; Minority stress; Pansexual; Physical health; Polysexual; dept.csp

LGBTQI+ Persons in Adulthood - Moore-Ramirez, A.; Kautzman-East, M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Due to their stigmatizing and marginalized experiences, as adults, LGBTQI+ people have variant developmental experiences for identity and intimacy. Their collegiate and occupational experiences may also be impacted by these negative experiences surrounding their LGBTQI+ identity. Experiences within the military are also covered within this chapter. The authors also discuss mid-life experiences for those within the LGBTQI+ population, including relationships, marriage, family planning and raising children. Issues facing the LGBTQI+ elderly population are also covered. © 2017 by the American Counseling Association. All rights reserved.
Keywords: Adulthood; Career; College; Development; Elderly; LGBT; dept.csp

Voices from the desks: exploring student experiences in counselor education - Foss-Kelly, Louisa L.; Protivnak, Jake J. (The Journal of Counselor Preparation and Supervision, 2017)
The purpose of the qualitative study was to explore the themes that counselor education master’s students perceived as impacting their experience within a counseling program. Counselor education master’s students provided their perceptions of what they attributed to helping or hindering their progress. Themes identified as impacting their experiences were academic environment, finances, job preparation, self-care, life role balance, support, mentoring and advising, and personal growth. Recommendations are provided for counselor educators to consider when structuring programs and interacting with master’s students.
Keywords: dept.csp

Counseling strategies for empowering people living in poverty: the I‐CARE model - Foss-Kelly, Louisa L.; Generali, Margaret M.; Kress, Victoria E. (Journal of Multicultural Counseling and Development, 2017)
Poverty has an impact on mental health and the counseling process in profound ways; however, counselors may fail to recognize the importance of poverty in clients' lives. The authors propose a model to help counselors navigate the complexities of counseling clients who are living in poverty. The I-CARE Model may help counselors develop insight about personal biases, acknowledge harsh realities of poverty, remove barriers to growth, and expand on the clients' own strengths.
Keywords: I-CARE Model; counseling; counselor; counselors; dept.csp; dura mater; human; human experiment; mental health; model; poverty; socioeconomic status

Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed

Interdependent group contingency to promote physical activity in children - Foote, Catherine; Bray, Melissa A.; Kehle, Thomas J.; VanHeest, Jaci L.; Gelbar, Nicholas W.; Byer-Alcorace, Gabriel; Maykel, Cheryl; DeBiase, Emily (Canadian Journal of School Psychology, 2017)
As the number of children affected by obesity increases in the United States, it is necessary to intervene with preventive and intervention techniques that will enact change. Because children spend a significant amount of their time in school, it is of particular interest to target strategies during the school day. Given the recommendations for the total duration and intensity of physical activity children should participate in, recess period is a means of acquiring a portion of this daily recommendation. Contingent reinforcement is a technique that is consistently used in schools to promote behavior change. One of these techniques, group contingencies, has repeatedly been shown to increase desired behavior and decrease inappropriate behavior in schools. In the present study, a multiple baseline design was utilized to investigate the use of interdependent group contingencies in physical activity performance during recess, as measured by pedometers, with one class from each of the third, fourth, and fifth grades at an elementary school. Some of the variability existed in gender- and body mass index-specific (BMI) subgroups, in regard to the effectiveness of the intervention and continued maintenance of increased physical activity levels, following the removal of the intervention. However, the overall results support the use of an interdependent group contingency intervention to increase the amount of physical activity students engaged in during recess.
Keywords: dept.csp; exercise; obesity; school-based treatment

Affirmative counseling with LGBTQI+ people - Ginicola, Misty M. (Amer Counseling Assn, 2017)
This current and comprehensive handbook will guide educators, students, and clinicians in developing the awareness, knowledge, and skills necessary to work effectively with LGBTQI+ populations. Twenty-five chapters written by experts in the field provide direction for working with clients in an authentic, ethical, and affirmative manner that is tailored to their individual strengths, needs, and identity. The book is divided into four sections, which explore the science behind gender and affectional orientation; developmental issues across the life span and treatment issues; the specialized needs of nine distinct populations; and the intersectionality of ethnicity and overlapping identities, the role of religion, and counselor advocacy. To further a deeper understanding of the content, each chapter contains an "Awareness of Attitudes and Beliefs Self-Check," a case narrative relating to the material covered, questions for discussion, and a list of online resources. The book concludes with an extensive glossary of terms, both preferred and problematic, which counselors working with these communities should understand and use appropriately. © 2017 by the American Counseling Association. All rights reserved.
Keywords: dept.csp

Do the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability? - Pagirsky, Matthew S.; Koriakin, Taylor A.; Avitia, Maria; Costa, Michael; Marchis, Lavinia; Maykel, Cheryl; Sassu, Kari; Bray, Melissa A.; Pan, Xingyu (Journal of Psychoeducational Assessment, 2017)
A large body of research has documented the relationship between attention-deficit hyperactivity disorder (ADHD) and reading difficulties in children; however, there have been no studies to date that have examined errors made by students with ADHD and reading difficulties. The present study sought to determine whether the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability. The participants in this study were 91 students in the ADHD clinical validity standardization sample of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3), as well as a control group of 63 students selected from the larger standardization sample. Students with ADHD and reading difficulties demonstrated a statistically significant greater amount of errors across tests of academic achievement. Findings from the study are discussed within the context of past research, as well as implications for the field of school psychology and practitioners.
Keywords: achievement; attention-deficit hyperactivity disorder; dept.csp; reading; special education

Biological gender differences in students’ errors on mathematics achievement tests - Stewart, Christie; Root, Melissa M.; Koriakin, Taylor; Choi, Dowon; Luria, Sarah R.; Bray, Melissa A.; Sassu, Kari; Maykel, Cheryl; O’Rourke, Patricia; Courville, Troy (Journal of Psychoeducational Assessment, 2017)
This study investigated developmental gender differences in mathematics achievement, using the child and adolescent portion (ages 6-19 years) of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3). Participants were divided into two age categories: 6 to 11 and 12 to 19. Error categories within the Math Concepts & Applications and Math Computation subtests of the KTEA-3 were factor analyzed and revealed five error factors. Multiple ANOVA of the error factor scores showed that, across both age categories, female and male mean scores were not significantly different across four error factors: math calculation, geometric concepts, basic math concepts, and addition. They were significantly different on the complex math problems error factor, with males performing better at the p ¡ .05 significance level for the 6 to 11 age group and at the p ¡ .001 significance level for the 12 to 19 age group. Implications in light of gender stereotype threat are discussed.
Keywords: KTEA-3; achievement; dept.csp; error analysis; factor analysis; gender; math

School counseling: Partnering with a school district to provide postsecondary opportunities for first generation, low income, and students of color - Perusse, Rachelle; Deronck, Nicole G; Parzych, Jennifer (Psychology in the Schools, 2017)
A classroom activity led by district school counselors was conducted in a K-12 school district to ensure educational equity for students in relation to postsecondary attendance. This took place in a school setting that has a large population of students of color, predominately Latino and African American students, as well as low-income students. As part of their practicum field experience, university school counseling students were supervised by school counselors at their sites to help provide a readily available and modified curriculum to instruct students about their options related to postsecondary awareness, planning, and attendance, as well as demonstrate career pathways that engender high expectations and college and career readiness. Instruction took place in the classroom as well as in small group settings.
Keywords: dept.csp; peer-reviewed; postsecondary opportunities